CILP1 interacting with YBX1 promotes hypertrophic scar formation by suppressing PPARs transcription - Jianzhang Wang; Juan Du; Yajuan Song; Xiaoying Tan; Junzheng Wu; Tong Wang; Yi Shi; Xingbo Xu; Zhou Yu; Baoqiang Song (Cell Death and Disease)
Abstract Hypertrophic scar (HS) represents the most prevalent form of skin fibrosis, significantly impacting the quality of life. Despite this, the molecular mechanisms driving HS formation remain largely undefined, impeding the development of effective treatments. The study showed that Cartilage Intermediate Layer Protein 1 (CILP1) was predominantly expressed in myofibroblasts and was up-regulated in various forms of skin fibrosis, including human hypertrophic and keloid scars, and in animal models of HS. Notably, we detected elevated serum levels of CILP1 in fifty-two patients with HS compared to twenty healthy individuals, suggesting its potential as a novel biomarker. The findings indicated that CILP1 was involved in a negative feedback loop with TGF-β and inhibited the transcription of Peroxisome Proliferator-Activated Receptors (PPARs) via interaction with Y-box-binding protein 1 (YBX1). This interaction promoted cell proliferation, migration, and collagen production in hypertrophic scar fibroblasts (HSFs). In vivo studies further confirmed that CILP1 knockdown markedly reduced HS formation, whereas administration of recombinant human CILP1 protein exacerbated it. These discoveries illuminated the CILP1-YBX1-PPARs signaling pathway as a key regulator of HS formation, offering a foundation for novel therapeutic approaches.